Method Development for the Analysis of Pharmaceuticals with Acethylcholinesterase Activity in Water Using HPLC-DAD and Solid Phase Extraction - Samuel Budi Wardhana; Marit Kolb; Müfit Bahadir; Bambang Purwono; Tutik Dwi Wahyuningsih (Indonesian Journal of Chemistry, 2014)
An SPE followed by HPLC-DAD method with ion pair chromatography technique to analyze pharmaceuticals with acethylcholinesterase activity including pyridostigmine (PYR), galathamine (GAL), neostigmine (NEO), eserine (ESE), and donepezil (DON) in water samples was developed. Acetylcholinesterase (AChE) inhibitors have been used to treat less severe dementias such as Alzheimer’s disease. Chromatographic separation was achieved using reversed-phase SymmetryShield column using gradient system with mobile phase consisting of H2O/ACN (99:1, v/v) as mobile phase A with 10 mM sodium 1-hexanesulfonate and 0.1% acetic acid (HAc). The HPLC/DAD method was linear between concentrations of 5 to 100 ng/μL. The IDL and IQL ranged from 0.50 to 1.25 ng/μL and 1.5 to 3.0 ng/μL, respectively. SPE was used to extract and clean up the target substances in spiked pure water, tap water, and wastewater samples. The application of extraction method of 5 target substances in wastewater sample was divided into 2 parts: Oasis WCX (6 mL, 500 mg) for PYR and Oasis HLB (6 mL, 200 mg) for GAL, NEO, ESE and DON. The developed SPE and HPLC/DAD method is applicable for quantification of the 5 target substances in water samples in a concentration range > 50 µg/L and assumable lower for DON (> 25 µg/L).